The Values of Moral Education in Shaping Islamic Personality In Era 4.0 Contained in the Book ‘I Left Him because of Him’ by Dunia Jilbab and Ririn Rahayu Astuti Ningrum - Rizal, Syamsul; Wahyuni, Sri (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2023)
Abstract The aim of this research is to find out what are the values ​​of moral education in forming an Islamic personality in the 4.0 era contained in the book ‘I left him because of him’ by Dunia Jilbab and Ririn Rahayu Astuti Ningrum. This research uses a type of library research (Library Research) with a qualitative approach. The data sources for this research are primary data, namely the book ‘I Leave Him Because of Him by Dunia Jilbab and Ririn Rahayu Astuti Ningrum, and secondary data, namely books or sources from other writings that discuss moral education. Then the data collection technique used in this research is documentation, where the researcher examines books related to the research object. The research results show that morals towards Allah SWT are piety, patience and sincerity, repentance, avoiding immorality, and dhikrullah. Morals towards family are birrul walidain and giving love to children, while morals towards fellow human beings are religious tolerance and mutual advice and encouragement to goodness. Morals towards oneself are not being excessive, being a Muslim woman is expensive, maintaining one's purity, improving oneself, utilizing one's time and having high ideals, and taking lessons from every trial.